Characterization of typical airborne fibrous particles and their aerodynamic removal - Zhang, Chengbin (2021)
Common fibers such as cotton, cottonwood seeds, and dryer lint can severely harm human health and equipment operation. In large quantities, fibers can clog air intakes and filters on equipment and machinery. Clogged air intakes and filters will lower efficiency, increase energy usage, causing overheating, premature failure, or explosions. Fibers can cause adverse health effects, from mild skin irritations to respiratory system impairment and suffocation. Fibers can stay airborne easily and travel a great distance. Small particles such as dust, bacteria, and viruses can attach to the fibers. However, there is a lack of information on the aerodynamic properties of such fibrous particles, which is critical for the proper design of air filtering systems such as HVAC systems and vehicles that encounter these particles. This research aims to characterize some commonly found fibrous particles' physical and aerodynamic properties and then develop and evaluate air cleaning prototypes to remove particles automatically from an air stream. The prototypes were designed based on the principle of a unique uniflow aerodynamic cyclone - the Deduster, developed at the Environment-Enhancing Energy Laboratory (E2-E Lab) led by Dr. Yuanhui Zhang at the University of Illinois at Urbana Champaign (UIUC) Various fibrous particle samples were collected and categorized into groups, including cotton, eastern cottonwood seeds, dandelions, grass residue (leaves), household dryer lint, Canada goose down feathers, and dog hairs. These particles are widely present, known to cause issues mentioned, and often caught on filters. The density of each sample group was measured using an analytical balance and a helium gas pycnometer. A distribution of aerodynamic diameters for each group was obtained by measuring particle settling velocity in a calm-air settling chamber. Conversions of dynamic shape factors and volume equivalent diameters were performed but only limited to Canada goose down feathers and grass residues due to their larger sizes. ...